UJI KINERJA RICE TRANSPLANTER ISEKI PC4 DI DESA KOPI KECAMATAN BINTAUNA - Fadlan Radjiku; Freeke Pangkerego; Frans Wenur (COCOS, 2018)
ABSTRACT Iseki PC4 Rice Transplanter is a rice paddy planting tool provided by the North Bolaang Mongondow district government assistance to farmers to help with the planting process so that it does not require a lot of human labor and can save on planting costs. However, until now the existing tools have not been used because farmers cannot operate them. For this reason, it is necessary to study the operation and performance of the tools so that farmers can use these tools and provide benefits. This study aims to determine the uniformity of seedling plugging, calculate field efficiency, and determine fuel consumption from the use of Iseki PC4 Rice Transplanter tools. The results of testing using Iseki PC4 Rice Transplanter obtained an average seed plugging uniformity of 86.73%, an average field efficiency of 78.58% and fuel consumption of 8.96 liters / ha. Keywords : Iseki PC4 Rice Transplanter, filed efficiency.